Effect of Trehalose and Glycerol on the Resistance of Recombinant Saccharomyces cerevisiae Strains to Desiccation, Freeze-thaw and Osmotic Stresses - Semkiv, M.V.; Ternavska, O.T.; Dmytruk, K.V.; Sibirny, A.A. (Наука та інновації, 2018)
Introduction. Baker's yeast Saccharomyces cerevisiae has been used for manufacturing bakery products, food and feed supplements, alcoholic fermentation etc. In biotechnological processes, yeast cells are exposed to stress factors (high concentration of sugars and ethanol, high temperature, desiccation or freezing etc.), which negatively affects their viability. Yeasts possess certain stress protection systems, including increased accumulation of disaccharide trehalose and glycerol synthesis. Problem Statement. The strengthening of yeast protective systems by increasing glycerol or trehalose concentrations can help to get increased stress robustness of the S. cerevisiae strains. Purpose. To construct the recombinant strains of S. cerevisiae with increased trehalose accumulation or glycerol production and to estimate the obtained recombinant strains resistance to a range of stress factors. Materials and Methods. S. сerevisiae transformation has been performed using Li-Ac-PEG method. Alcoholic fermentation has been carried out at a temperature of 30 °C with stirring at a rate of 120 rpm. Results. The recombinant strains of S. cerevisiae with enhanced glycerol production (up to 19 g/L) have been constructed based on BY4742. The industrial ethanol-producing strain Y-563 has been used as parental one for construction of recombinant strains with up to 3.3-fold increase in the intracellular trehalose level. The resistance of obtained recombinant strains to different stress factors has been evaluated. BY/TPI25/gpd1gpp2f/fps1 strain with the highest glycerol production has been established to have the highest osmotolerance. The BY/TPI25/gpd1gpp2f, 563/TSL1, 563/TPS1/2 and 563/TPS1/2/TSL1 strains have shown higher viability after freeze-thaw as compared with the corresponding parental strains, but not higher resistance to desiccation. The recombinant strain 563/TPS1/2/TSL1 with a high trehalose content have been established to have higher activity during fermentation of sugar in sweet dough and to longer keep stable at 35 °С as compared with the initial strain Y-563. Conclusions. Constructed recombinant strains of S. cerevisiae with higher osmotolerance or freeze-thaw resistance can be implemented in industrial processes accompanied with these types of stresses. Baker's yeast made of high trehalose- containing biomass will have prolonged shelf life.